Influence of Ni/Mo ratio on structural and electrical properties of double perovskite system Sr2Ni1+xMo1−xO6−δ - Kumar P.; Singh N.K.; Singh R.K.; Singh P. (My University, 2025)
Technologically important double perovskite system Sr2Ni1+xMo1−xO6−δ with x = 0.00, 0.05, 0.10, and 0.15 was prepared by solution combustion method. The structural and the Rietveld analysis of compositions revealed the formation of double perovskite tetragonal phase Sr2NiMoO6 with space group I4/m as a major phase. SrMoO4 and NiO were also observed as minor phases. Microstructural studies depicted the formation of uniform grains for all the samples. The average grain size was found to lie between the ranges of 1–4 μm. XPS analysis of the synthesized compositions showed the decreasing ratio of Mo5+ to Mo6+ ions in the system with increasing Ni content, which played an important role in the conduction mechanism. The thermal expansion coefficient (TEC) of all compositions indicated that it is more compatible to the TEC of standard electrolytes. The electrical conductivity for all the compositions was studied using impedance spectroscopy in the temperature range 200–600 °C. Composition with x = 0.05 showed better electrical conductivity with good catalytic activity. © 2015, Springer-Verlag Berlin Heidelberg.